ANALYZING STUDENTS CHALLENGES ON READING COMPREHENSION THROUGH ENGLISH TEXTBOOKS - Meisya Nur Hidayah; Deri Sis Nanda (Universitas 17 Agustus 1945 Semarang, 2025)
Reading is a vital skill for knowledge acquisition, yet many students struggle due to pronunciation challenges influenced by their native language, limited vocabulary, and ineffective reading strategies. This study aims to analyze the students challenge on reading comprehension through English text book faced by 11th-grade Multimedia. Using a descriptive qualitative approach, the research involved observations and questionnaires administered to a sample of 15 students who scored below 70 on their first-semester exams. Findings revealed that pronunciation issues hindered reading fluency and comprehension, corroborating previous studies that indicated high percentages of difficulty in identifying detailed information and understanding text structure. While some students displayed progress in vocabulary response, overall comprehension remained a significant challenge. This research underscores the necessity for targeted instructional strategies that address pronunciation, vocabulary development, and reading fluency. Ultimately, the study highlights the importance of a comprehensive approach to enhance reading comprehension, thereby fostering greater engagement with English texts among students.